2012
DOI: 10.1016/j.physletb.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Study of the surrogate-reaction method applied to neutron-induced capture cross sections

Abstract: 174Yb(3He,αγ )173Yb* and 174Yb(3He,pγ )176Lu*, respectively. For the first time, the gamma-decay probabilities have been obtained with two independent experimental methods based on the use of C6D6 scintillators and Germanium detectors. Our results for the radiative-capture cross sections are several times higher than the corresponding neutron-induced data. To explain these differences, we have used our gamma-decay probabilities to extract rather direct information on the spin distributions populated in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 18 publications
7
63
1
Order By: Relevance
“…Many experiments have shown a trend that the surrogate reactions tend to preferably populate higher J than the direct measurements using neutron beams [15,21,24]. The present results indicate that (p, p ) populates much lower J states than (p, d) and (p, t), therefore it is possible that (p, p ) provides a better surrogate for the direct measurements than (p, d) and (p, t) reactions.…”
Section: Toward the Application To The Surrogate Reaction Approachsupporting
confidence: 46%
See 2 more Smart Citations
“…Many experiments have shown a trend that the surrogate reactions tend to preferably populate higher J than the direct measurements using neutron beams [15,21,24]. The present results indicate that (p, p ) populates much lower J states than (p, d) and (p, t), therefore it is possible that (p, p ) provides a better surrogate for the direct measurements than (p, d) and (p, t) reactions.…”
Section: Toward the Application To The Surrogate Reaction Approachsupporting
confidence: 46%
“…While this has a smaller effect on the extraction of fission cross sections [9], the γ-ray emission of the compound nucleus can be quite sensitive to the initial J π distribution [14,15,[17][18][19][20][21]. Therefore, in order to extract (n, γ) cross sections from surrogate data it becomes necessary to take into account the J π distribution of the decaying compound nucleus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4]) showed a very good agreement of the fission cross sections obtained with the surrogate and direct methods for actinides. However, in recent experiments [5,6] radiative capture cross sections on rare earths obtained in surrogate reactions were found to be higher up to a factor of 10 than the corresponding neutron-induced reaction data. These important discrepancies were attributed to the large differences in the angular momentum between the mother and the daughter nuclei around the neutron separation energy, which results in the hindering of the neutron emission channel and therefore in the increase of the gamma emission probability [6].…”
Section: Introductionmentioning
confidence: 86%
“…While the applicability of the surrogate reaction approach has been demonstrated for (n,f) cross sections [8][9][10][11][12], it has been difficult to determine (n,J) cross sections due primarily to the discrepancy in the spin-parity distributions of the compound nucleus created by the (n,J) and the surrogate reaction [13][14][15][16][17]. However, some recent research showed promise for inferring (n,J) cross sections by accounting for spin-parity distribution of the compound nucleus [18].…”
Section: Introductionmentioning
confidence: 99%